The effect of vocal fold vertical stiffness variation on voice production - Geng, Biao (J Acoust Soc Am, 2016)
A parametric study was conducted using the numerical technique that coupled a three-dimensional continuum vocal fold model with a one-dimensional Bernoulli flow model to investigate the effect of vocal fold vertical stiffness variation on voice production. Vertical stiffness gradient was defined as the ratio of the inferior–superior stiffness difference to the mean stiffness and was introduced in the cover layer. The results showed that increasing the vertical stiffness gradient would increase the peak flow rate and sound intensity and decrease the open quotient and threshold pressure. The effect was found to be more prominent at low subglottal pressures. The underlying mechanism might be that the reduced stiffness at the superior aspect of the vocal fold would allow a larger lateral displacement and result in a larger vibration. Increasing the vertical stiffness gradient was also found to increase the vertical phase difference and glottal divergent angle during the vocal fold vibration. Meanwhile, increasing the vertical stiffness variation only slightly increased the mean flow rate, which is important to maintaining the speech time between breaths.